The Influence of the Cashless Policy on Economic Growth and Development - Ogunlade, Deborah Adesoye; Amodu, Muhammed Abdulasisi (NIU Journal of Social Sciences, 2024)
The study investigates the correlation between the cashless policy and economic growth and development in Nigeria. Ordinary regression analysis was applied to assess the impact of the cashless policy on economic growth and development. Data were gathered from participants using a structured questionnaire. The study's results demonstrated that the independent variables (EBS, ETS, P2P) exert a significant influence on the dependent variable (EGD). The notably high R-squared value indicates a strong alignment of the model with the data. Conclusively, the study asserts that the cashless policy exhibits a substantial positive impact on economic growth and development in Nigeria. Consequently, it suggests that governmental bodies and those in authoritative positions should implement initiatives aimed at enhancing digital financial literacy among the populace, fostering effective utilization of electronic banking systems, electronic transfer systems, and peer-to-peer payment platforms. Keywords: Economic Growth and Development; Electronic Banking System; Electronic Transfer System; Peer-To-Peer (P2P) Payments